2022
DOI: 10.1001/jamanetworkopen.2021.43363
|View full text |Cite
|
Sign up to set email alerts
|

Income Support as a Health Intervention

Abstract: The increasing recognition of social and economic factors as fundamental to health and health disparities has dramatically broadened the topics, levels of analysis, and interventions considered relevant to public health and medicine. The article by Shafer and colleagues 1 is an excellent example of this broader orientation. The authors examined the short-term associations of giving most US families with children an advanced monthly payment on a substantial tax credit with food insufficiency. Household food ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Low basic income constitutes a major health constraint [ 66 ], associated with increased food insecurity [ 67 ]. Economic analyses of the reference diet have revealed that the cost of the diet exceeded the household/capita income of at least 1.58 billion people worldwide, making it unaffordable [ 68 , 69 , 70 ].…”
Section: The Eat- Lancet Reference Dietmentioning
confidence: 99%
“…Low basic income constitutes a major health constraint [ 66 ], associated with increased food insecurity [ 67 ]. Economic analyses of the reference diet have revealed that the cost of the diet exceeded the household/capita income of at least 1.58 billion people worldwide, making it unaffordable [ 68 , 69 , 70 ].…”
Section: The Eat- Lancet Reference Dietmentioning
confidence: 99%